The effect of fever tea tree (lippia javanica) in the control of maize weevil (sitophilus zeamais) in stored maize (zea mays) - Majoro, Mordester (Midlands State University, 2018)
Sitophilus zeamais Motschulsky is the major insect pest seen damaging stored maize in Zimbabwe. The environmental hazards of synthetic insecticides, the unreliability supply and high costs of these chemicals resulted in the search for cheaper and safer use of the naturally available plant material to control this pest. This study evaluates effective rates for L. javanica leaf powder. Bioactivity of Lippia javanica leaf extracts was evaluated under average room temperature, at three dosage levels (0. 5g, 10g and 15g),negative control of untreated grain were mixed with 1kg of disinfested Pannar 413 maize variety in plastic containers. A positive control of Actellic Gold Dust was also used at label rates and the effect on grain damage, weight loss, insect mortality; progeny production was assessed. The leaf extract showed significant difference between 0.5g and 10g on one hand and 15g and the positive control showed no statistical difference. The 15g that recorded the highest mortality inflicted 85.25%. The maize grain treated with 10g and 15g dosage levels of the leaf extract showed much promise by significantly reducing the number of damaged grains by the maize weevil, reproduction of the maize weevilas well as reducing weight loss in stored maize compared with the negative control. Grain weight loss in leaf powder treated grains was dose dependent ranging from 4% in the highest dose to 44.6% with untreated grain at 59% in untreated maize grain showing significant differences in 21 days